Eccentric left ventricular hypertrophy, left and right cardiac function in Chronic Heart Failure with or without coexisting COPD: impact on exercise performance - Santos, Polliana Batista dos (2021)
Abstract Aim: Our aim was to assess: 1) the impact of the eccentric left ventricular hypertrophy (ELVH) on exercise performance in patients diagnosed with chronic heart failure (CHF) alone and in patients with co-existing CHF and chronic obstructive pulmonary disease (COPD) and 2) the relationship between left and right cardiac function measurements obtained by doppler echocardiography, clinical characteristics and primary measures of cardiorespiratory fitness. Methods: The current study included 46 patients (CHF:23 and CHF+COPD:23) that performed advanced pulmonary function tests, echocardiography and symptom-limited, incremental cardiopulmonary exercise testing (CPET) on a cycle ergometer. Results: Patients with CHF+COPD demonstrated a lower work rate, peak oxygen uptake (VO2), oxygen pulse, rate pressure product (RPP), circulatory power (CP) and ventilatory power (VP) compared to those only diagnosed with CHF. In addition, significant correlations were observed between VP and relative wall thickness (r: 0.45 p: 0.03),VE/VCO2 intercept and Mitral E/e' ratio (r: 0.70 p: 0.003) in the CHF group. Significant correlations were found between indexed left ventricle mass and RPP (r: -0.47; p: 0.02) and relative VO2 and right ventricle diameter (r: -0.62; p: 0.001) in the CHF+COPD group. Conclusion: Compared to a diagnosis of CHF alone, a combined diagnosis of CHF+COPD induced further impairments in cardiorespiratory fitness. Moreover, echocardiographic measures of cardiac function are related to cardiopulmonary exercise performance and therefore appear to be an important therapeutic target when attempting to improve exercise performance and functional capacity.